Vivre dans deux temps - Davide Mano (Recherches, 2021)
This article offers a first analysis of the Jewish lunar calendars published in Italy between the 18th century and the 20th century. Tools of daily use linking agricultural work to community life, as well as instruments for religious and political education, or for cultural and scientific popularization, these documents show the centrality of the articulation of the two times—Jewish time and popular time—in the social, economic, political and cultural life of Italian Jews. The changes in the organization of these calendars over the centuries reflect the different times and modalities of the process of Jewish emancipation, a long and non-linear process of back and forth. This article thus deals with the times of the Jews at the two turning points of the revolutionary era and of the Unity of Italy.